Ethical Meaning of Philosophy - Kapačiauskienė, Danutė (Problemos, 1990)
Philosophy serves as a methodology for ethics in a sense that it creates with the concept of being the definitely oriented space, in which ethics formulates its own criteria of morality. The meaning of ethics for philosophy is existential one. In order to formulate the criteria, ethics must have the understanding of what is good. The question is addressed to a philosopher which, on its tum, is compelled to think of being as good, and thus the existence of philosophy as a human phenomenon is backed. That is why there is no philosophy without ethics and there is no ethics without philosophy. At the point of the fusion of the two the problem of the sense of human comes into being. In the paper the relations between Marxist philosophy and ethics are analysed too.